Peningkatan Ketahanan Pangan Melalui Hidroponik Wick Syistem Di Desa Blok 31 Kecamatan Gunung Meriah Sebagai Upaya Pencegahan Stunting - Safril Maulida; Sahirman; Laode Irdana; Mauliza; Salumaiyah; Nariza Yanti; Intan Badola; Halimah; Teuku Nih Farisni (Pusat Penelitian dan Pengabdian Kepada Masyarakat STAIN Teungku Dirundeng Meulaboh, 2025)
Stunting remains a critical health issue in Indonesia, particularly in regions with limited access to nutritious food. This research aims to strengthen food security through the implementation of Wick system hydroponic technology in Blok 31 Village, Gunung Meriah District, as a stunting prevention measure. The program was conducted over 30 days using participatory action research methods, involving collaboration between the KKN team, village officials, and local community members. The program implementation consisted of three phases: (1) socialization and problem identification, (2) training and hydroponic system construction, and (3) monitoring and evaluation. Results indicated that the Wick system hydroponic technology was successfully adopted by the community due to its ease of implementation and cost-effectiveness. This system enables independent production of vegetables and fruits in limited spaces, increasing household access to nutritious food. The program contributes to strengthening local food security and stunting prevention efforts through sustainable access to nutritious food supplies.